Optimized downdraft rice husk furnace for paddy drying - CGIAR Research Program on Rice (2019)
The technology was transferred to the private companies in the Philippines, Indonesia, Vietnam, Myanmar, and Cambodia. About 200, 40, and several units were already used for paddy drying in the Philippines, Indonesia, and Cambodia, respectively.